2022
DOI: 10.1088/1757-899x/1220/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of vehicles aerodynamics in platoon using CFD simulation

Abstract: Due to increased traffic and new technologies developed to improve road safety, a new vehicle driving technique is being studied. The vehicles’ platooning driving method has as objective to minimize the aerodynamic drag and therefore the fuel consumption. The aim of this study is to evaluate the distance between platoon traveling vehicles and to propose an optimal travel distance. The CFD evaluation is performed for two categories of vehicles at a given velocity and distance between them for two cases: in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Second, many research institutions and universities are also actively studying the aerodynamic performance of cars. For example, institutions such as NASA 8 in the United States and Fraunhofer 9 in Germany are conducting research on vehicle aerodynamics and have proposed many new theories and methods. Many international universities have also set up related courses and majors, and has trained many professionals in this research direction 10 .…”
Section: Current Status Of Foreign Researchmentioning
confidence: 99%
“…Second, many research institutions and universities are also actively studying the aerodynamic performance of cars. For example, institutions such as NASA 8 in the United States and Fraunhofer 9 in Germany are conducting research on vehicle aerodynamics and have proposed many new theories and methods. Many international universities have also set up related courses and majors, and has trained many professionals in this research direction 10 .…”
Section: Current Status Of Foreign Researchmentioning
confidence: 99%
“…A computational fluid dynamics (CFD) model serves as a numerical tool to simulate the complex airflow dynamics resulting from the interaction of multiple vehicles. Numerous studies have utilized CFD to model HDV platooning, revealing that a platooning configuration significantly reduces aerodynamic drag [22,[28][29][30]. Smith et al [31] and Vegendla et al [32] reported simulated drag savings of up to 23% at a separation distance of 30 feet with two vehicles.…”
Section: Introductionmentioning
confidence: 99%